2017
DOI: 10.1186/s40104-017-0201-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant and native buffalo OVGP1 on sperm functions and in vitro embryo development: a comparative study

Abstract: BackgroundAn oviduct- specific glycoprotein, OVGP1, is synthesized and secreted by non-ciliated epithelial cells of the mammalian oviduct which provides an essential milieu for reproductive functions. The present study reports the effects of recombinant buffalo OVGP1 that lacks post-translational modifications, and native Buffalo OVGP1 isolated from oviductal tissue, on frozen- thawed sperm functions and in vitro embryo development.ResultsThe proportion of viable sperms was greater (P < 0.05) in the recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…Recently, a study in water buffalo also reported that there was no difference in terms of blastocyst production rate following IVF with frozen-thawed sperm of a cloned Murrah bull and its donor [ 6 ], although they did not examine cleavage rates and quality of produced blastocysts. This study had low blastocyst rates (~10%), which is in agreement with other IVF studies in buffalos [ 29 32 ]. The laboratory-to-laboratory variations, conditions, protocols, and other factors could have contributed variation in IVF results [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a study in water buffalo also reported that there was no difference in terms of blastocyst production rate following IVF with frozen-thawed sperm of a cloned Murrah bull and its donor [ 6 ], although they did not examine cleavage rates and quality of produced blastocysts. This study had low blastocyst rates (~10%), which is in agreement with other IVF studies in buffalos [ 29 32 ]. The laboratory-to-laboratory variations, conditions, protocols, and other factors could have contributed variation in IVF results [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Some roles played by oviductin on early embryo development were reported from in vitro studies. Consistent positive effects of purified oviductin were observed on blastocyst yield in goat [17], sheep [40], pig [41] and cattle [18]. Antibodies directed against the C-terminal peptide of rabbit oviductin were shown to inhibit mouse embryo development at the 2-cell stage, suggesting that in this species, oviductin has a function in overcoming the development block at this stage [42].…”
Section: Discussionmentioning
confidence: 71%
“…The proteins present in the OF, either within EVs or as soluble molecules, may play key roles in supporting embryo development. Indeed, the addition of purified or recombinant oviductin, an oviduct-specific estrus-induced glycoprotein, to the culture medium was reported to increase the rates of blastocyst development of goat [17] and cattle [18] embryos compared with non-supplemented controls. In another study, the presence of porcine recombinant oviductin did not enhance in vitro developmental rates but produced bovine blastocysts of higher quality regarding the expression of specific genes [19].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we identified 63 ODF proteins that are important for the early reproductive processes. Some of these proteins, including LTF, HSPA5, and OVGP1 have previously been shown to modify reproductive processes in vitro. Changes in the abundance of diverse immunity proteins, such as CD109 and members of the S100 family, were also induced by insemination.…”
Section: Discussionmentioning
confidence: 99%